Business sense needed from growers and government - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Joseph Nkole of the Cotton Producers? Association of Zambia on the farmer practices and government policies needed to support the industry.